Nonlinear quenching of excitonic emission from nanoplatelet films at high excitation densities - Simon Jessen; Alessio Di Giacomo; Iwan Moreels; Brian Julsgaard; Rosana M. Turtos (Scientific Reports)
Abstract The conversion of gamma particles into optical photons in state-of-the-art scintillator materials is limited to maximum 10 emitted photons per MeV of energy deposited per picosecond, when the material is excited at room-temperature. Breaking this limit has both fundamental and applied importance, and motivates the search for fast and efficient optical emitters at excitation densities relevant for particle detection, up to 1020 electron–hole pairs (eh) per cm3. In this work, we address this challenge by probing the optical response of a promising nanomaterial, CdSe/CdS core/crown nanoplatelets (NPLs), in the shape of drop cast films using intense femtosecond laser pulses. The study finds that the NPL films exhibit a bright optical response at low to medium excitation densities but suffer from high levels of nonlinear quenching, dominated by exciton-exciton annihilation (EEA), at densities exceeding 1017 eh/cm3. The experimental data and theoretical calculations suggest that EEA is enhanced in the drop cast film by the close packing of NPLs which allows excitons to migrate between NPLs in the film. Despite this, light yield estimations based on a simulated distribution of excitation densities predict values upwards of 2000 ph/MeV, while showing ample room for improvement and the future potential of surpassing the 10 ph/MeV/ps benchmark.